Finite element analysis on the static and fatigue characteristics of composite multi-leaf spring - Kueh J.-T.J.; Faris T. (2023)
This paper investigated the static and fatigue behaviors of steel and composite multi-leaf spring using the ANSYS V12 software. The dimensions of an existing conventional leaf spring of a light commercial vehicle were used. The same dimensions were used to design composite multi-leaf spring for the two materials, E-glass fiber/epoxy and E-glass fiber/vinyl ester, which are of great interest to the transportation industry. Main consideration was given to the effects of material composition and its fiber orientation on the static and fatigue behaviors of leaf spring. The design constraints were bending stresses, deflection and fatigue life. Compared to the steel leaf spring, the designed composite spring has much lower bending stresses and deflections and higher fatigue life cycles. 2012 Zhejiang University and Springer-Verlag Berlin Heidelberg.